Isolation and identification of java race amniotic membrane secretory leukocyte protease inhibitor gene - Elly Munadziroh (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Secretory leukocyte protease inhibitor (SLPI) has been found to facilitate epithelialization, maintain a normal epithelial phenotype, reduce inflammation, secrete growth factors such as IL-4, IL-6, IL-10, EGF, FGF, TGF, HGFand 2-microbulin. SLPI is serine protease inhibitor, which found in secretions such as whole saliva, seminal fluid, cervical mucus, synovial fluid, breast milk, tears, amniotic fluid and amniotic membrane. Impaired healing states are characterized by excessive proteolysis and oftenbacterial infection, leading to the hypothesis that SLPI may have a role in the healing process in oral inflammation and contributes to tissue repair in oral mucosa. The oral wound healing response is impaired in the SLPI sufficient mice since matrix synthesis and collagen deposition delayed. The objective of this research is to isolate and identify the amniotic membrane of Java Race SLPI Gene. Methods: SLPI RNA was isolated from Java Race amniotic membrane and the cDNA was amplified by polymerase chain reaction (PCR). Result: Through sequence analyses, SLPI cDNA was 530 nucleotide in length with a predicted molecular mass about 12 kDa. The nucleotide sequence showed that human SLPI from sample was 98% identical with human SLPI from gene bank. PCR analysis revealed that the mRNA of SLPI was highly expressed in the amniotic membrane from Java Race sample. Conclusion: it is demonstrated that human SLPI are highly conserved in sequence content as compared to the human SLPI from gene.